80/5000 Liceu Vieira Dias and N’gola Ritmos: music and anti-colonial resistance in Angola - Nascimento, Washington Santos (ODEERE, 2016)
This article’s purpose is to make a discussion of music and anticolonial resistance in Angola from the history of Liceu Vieira Dias and N’gola Rhythms musical group. Therefore we will follow the path of Liceu and N’gola, how they used music as resistance and as group members acted in clandestine of the metropolitan government defense organizations before 1961. Keywords: Angola, Music, Resistance